2016
DOI: 10.1016/j.cell.2016.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Splicing of Nascent RNA Coincides with Intron Exit from RNA Polymerase II

Abstract: Summary Protein-coding genes in eukaryotes are transcribed by RNA polymerase II (Pol II) and introns are removed from pre-mRNA by the spliceosome. Understanding the time lag between Pol II progression and splicing could provide mechanistic insights into the regulation of gene expression. Here we present two single molecule nascent RNA sequencing methods that directly determine the progress of splicing catalysis as a function of Pol II position. Endogenous genes were analyzed on a global scale in budding yeast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
203
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(233 citation statements)
references
References 54 publications
20
203
2
Order By: Relevance
“…The average position for onset (10% of transcripts spliced) of 26 nt after transcription of the 3 ′ splice site is remarkably soon given that the distance between polymerase and spliceosome active sites is estimated as 24 nt (Carrillo Oesterreich et al 2016). Perhaps this is not surprising: In a first-order kinetics approximation of splicing, the relative time or position of splicing would be an exponential distribution, with a mode at the first available point.…”
Section: Smit (Carrillo Oesterreich Et Al 2016)mentioning
confidence: 99%
See 3 more Smart Citations
“…The average position for onset (10% of transcripts spliced) of 26 nt after transcription of the 3 ′ splice site is remarkably soon given that the distance between polymerase and spliceosome active sites is estimated as 24 nt (Carrillo Oesterreich et al 2016). Perhaps this is not surprising: In a first-order kinetics approximation of splicing, the relative time or position of splicing would be an exponential distribution, with a mode at the first available point.…”
Section: Smit (Carrillo Oesterreich Et Al 2016)mentioning
confidence: 99%
“…Do these observations extend to other eukaryotes? For Schizosaccharomyces pombe, fast, cotranscriptional splicing was reported by long-read sequencing (Carrillo Oesterreich et al 2016) and suggested by 4tU-seq (Eser et al 2016). NET-seq in mammals supports cotranscriptional splicing, observing Pol II peaks (interpreted as transcriptional pauses) 3…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is, in part, because the splicing machinery acts in a co-transcriptional manner to quickly remove most introns as soon as they have been fully transcribed by RNA polymerase II. [18][19][20] By the time a given splice donor (5 0 splice site) is transcribed, all of the upstream splice acceptors (3 0 splice sites) in that pre-mRNA have usually been removed, making backsplicing impossible. However, there are an increasing number of introns that are known to be slowly or post-transcriptionally spliced.…”
Section: Introductionmentioning
confidence: 99%